(3TQM eG jbY ajg GdJUMja hGdJMQjas - (3CHh CMeO,J (B382 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeg hLejd UfYg TQMJ ai cJGHi gPG GdCdaGX hGdCSeGA GdeTcdI GdJi JJTGHg ai UhQI GdNW ajbY ajgG GdJUMja hjONdgG GdJMQja s
(3BNQgG (B:s
(3hbO TP ef GdHGH CTjGA efgG GdeSLO hGdeWdY Ydi ePgH ef bQC eWdY GdaLQ , aEf CUdg ai GdfMh WdY jWdY , hSLO jSLO s
(3GdNW eged GdfbW CMjGfG hHgG CKQ WeSs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196s
Keywords: (3GddZIs